Hope and a future : perspectives on the impact that librarians and libraries have on our world - Hill, Renee F. (Advances in librarianship ;, 2021)
In a world that often questions the value of libraries and librarianship, this collection of reflective essays and future-focused research emphasizes the ways in which being an information professional continues to be a rewarding and vital profession. Including sixteen chapters written by library practitioners, researchers, and educators, this book covers topics, among others, such as the impact of K-12 school librarians on media literacy, the community power of public libraries, the transformative power of community-focused library collaborations, and strategies for implementing effective outreach for underserved populations. It is by sharing their thoughtful, vibrant, and at times painfully honest perspectives on the varied and essential roles that librarians and libraries play in our world that the authors display their passion for librarianship and demonstrate why continued support for libraries is essential.